CCND2 mRNA Expression Is Correlated With R-CHOP Treatment Efficacy and Prognosis in Patients With ABC-DLBCL - Wang, Di; Zhang, Yue; Che, Yi-Qun (Frontiers in Oncology, 2020)
In this study we investigated whether the expression of cyclin D2 (CCND2) mRNA in activated B-cell-like diffuse large B-cell lymphoma (ABC-DLBCL) was correlated with the efficacy of Rituximab combined with chemotherapy (R-CHOP) treatment and patient prognosis. Tissue microarray and RNAscope in situ hybridization were used to detect CCND2 mRNA expression in 117 ABC-DLBCL tumor tissues and associations between CCND2 expression and progression-free survival was analyzed. We also downloaded data from the Gene Expression Omnibus database to analyze CCND2 expression and the efficacy of R-CHOP treatment and prognosis of patients with newly diagnosed ABC-DLBCL. The positive expression rate of CCND2 mRNA in patients with ABC-DLBCL was 41%. Progression-free survival was significantly lower in patients with positive rather with than those negative CCND2 expression (P = 0.005). Further, R-CHOP treatment was significantly more effective for patients with ABC-DLBCL with high CCND2 mRNA expression than those with low expression (P = 0.039). Multivariate regression analysis suggested that high CCND2 expression was an independent prognostic risk factor for patients with ABC-DLBCL who achieved complete remission after R-CHOP treatment. CCND2 expression in ABC-DLBCL tumors, detected by RNA in situ hybridization, is closely related to the curative effect of R-CHOP and patient prognosis following R-CHOP treatment, and represents a potential biomarker for treatment efficacy and prognostic evaluation in patients with ABC-DLBCL.